The plant-based chimeric antimicrobial protein SlP14a-PPC20 protects tomato against bacterial wilt disease caused by Ralstonia solanacearum. (March 2019) - Morais, Tâmara P.; Zaini, Paulo A.; Chakraborty, Sandeep; Gouran, Hossein; Carvalho, Camila P.; Almeida-Souza, Hebréia O.; Souza, Jessica B.; Santos, Paula S.; Goulart, Luiz R.; Luz, José M.Q.; Nascimento, Rafael; Dandekar, Abhaya M.
Highlights: SCALPEL identifies antimicrobial peptides based on amphipathic cationic properties. Plant-derived antimicrobial peptides inhibit the growth of Ralstonia solanacearum. Cisgenic approach resulted in tomato lines resistant to bacterial wilt disease. Abstract: Cecropin-B (CecB) is a peptide with well-established antimicrobial properties against different phytopathogenic bacteria. Despite modest action against Ralstonia solanacearum, its animal source limits the acceptance in transgenic applications. To overcome this, we selected eight alpha-helical (AH) cationic peptides derived from plant protein sequences and investigated their antimicrobial properties against R. solanacearum . Remarkably, PPC20 (a linear AH-peptide present in phosphoenolpyruvate carboxylase) has a three-fold lower lethal dose on R. solanacearum than CecB and lower toxicity to human intestinal epithelial cells. Linking PPC20 to SlP14a (part of a pathogenesis-related protein) established an apoplast-targeted protein providing a means of secreting and stabilizing the antimicrobial peptide in the plant compartment colonized by the pathogen. SlP14a is also a potential antimicrobial, homologous to a human elastase which likely targets outer membrane proteins in Gram-negative bacteria. Recombinant SlP14a-PPC20 showed antibacterial activity against R. solanacearum in vitro, making it a promising candidate for plant protection. This was confirmed with genetically-modified tomato plants engineered to express SlP14a-PPC20, in which bacterial populations in stems were reduced compared to inoculated wild-type control plants. Disease symptoms were also markedly less severe in SlP14a-PPC20-expressing plants, demonstrating a viable strategy to improve resistance against bacterial wilt in tomato.